2012
DOI: 10.1080/00207594.2011.649285
|View full text |Cite
|
Sign up to set email alerts
|

Cultural influences on Facebook photographs

Abstract: Prior research in social psychology indicates that East Asians from collectivistic and interdependent sociocultural systems are more sensitive to contextual information than Westerners, whereas Westerners with individualistic and independent representation have a tendency to process focal and discrete attributes of the environment. Here we have demonstrated that such systematic cultural variations can also be observed in cyberspace, focusing on self-presentation of photographs on Facebook, the most popular wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 33 publications
1
55
0
Order By: Relevance
“…Furthermore, we believe that the expressions of many individuals reflect cultural differences in ideal affect, not just those of leaders. Indeed, although they did not link their findings to ideal affect, Huang & Park (2013) observed that American Facebook pages had higher intensity smiles than Taiwanese Facebook pages. Similarly, we observed that American storybook characters showed more excited and fewer calm smiles than Taiwanese storybook characters (Tsai et al, 2007)), suggesting that these differences are not specific to leaders.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, we believe that the expressions of many individuals reflect cultural differences in ideal affect, not just those of leaders. Indeed, although they did not link their findings to ideal affect, Huang & Park (2013) observed that American Facebook pages had higher intensity smiles than Taiwanese Facebook pages. Similarly, we observed that American storybook characters showed more excited and fewer calm smiles than Taiwanese storybook characters (Tsai et al, 2007)), suggesting that these differences are not specific to leaders.…”
Section: Discussionmentioning
confidence: 90%
“…The collectivistic characteristics of Asian young people and the individualist characteristics of Western young people have been found to affect their behavioral patterns on Facebook. 36 We believe that such differences may also help to explain the higher use of online social networking in Asian adolescents. One cultural similarity across China, Japan, and South Korea is Neo-Confucianism, which may suppress individualism and the expression of individual creativity.…”
Section: Discussionmentioning
confidence: 98%
“…Conversely, these two universities may have cultural differences regarding what is acceptable to display on Facebook. Previous work evaluated differences in two countries’ cultures in what level of personal information is acceptable or desirable to display on Facebook and found marked differences (Huang & Park, 2012). In contrast, findings in this study derive from similar populations of college students at large state universities who are displaced by location in the country.…”
Section: Discussionmentioning
confidence: 99%